Using precision medicine to individualize healthcare. Issue 8 (August 2019) - Key, Betty A.; Mumba, Mercy
Abstract : Abstract: The Precision Medicine Initiative (PMI) is a government initiative to encourage individualized care. This article provides a snapshot of precision medicine and its implications for patients and study participants, as well as the PMI and the role of nurses as educated patient advocates. Abstract : Explore nursing's role in the Precision Medicine Initiative, which is intended to encourage individualized care and increase the number of minority and underrepresented patients in clinical research.